ORTHOPTERA (INSECTA) FROM MUZAFFARNAGAR, A TERAI DISTRICT INNORTH-WEST OF UPPER INDO-GANGETIC PLAIN, INDIA - GOEL, S.C.; GUPTA, SUNIL KUMAR; GUPTA, DEVANSHU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
The grasshoppers and locusts together with nymphs are the destructive insect defoliating the uncultivated and cultivated green vegetations and belong to the superfamily Acridoidea under Orthoptera (Insecta). The present study has been undertaken to characterize the Orthopteran insects of Muzaffarnagar in particular, situated as a part of north-west of Upper Indo-Gangetic plain, located at the base of Himalayan and Shivalik ranges. This part has been recorded with 33 species under 26 genera from 14 subfamilies and 08 families. A few species like Acrida exaltata, Trilophida annualata, Aiolopus thalassimmus tamulus, Hieroglyphus banian, Oxya velox and sorted out in common north of Himachal Pradesh to deep south up to Bihar and Madhya Pradesh. Perhaps the reason had been that these remain tolerant to change in climatology like monsoon rain, and physiography of soil to lay their eggs in large number. It has been concluded that these phototaxic species are reported from every part of Uttar Pradesh.